Exploring A 2 Million + Year Ice Climate Archive-Allan Hills Blue Ice Area (2MBIA) - Bender, Michael (IEDA: US Antarctic Program Data Center, 2014)
Abstract: This award supports a project to generate an absolute timescale for the Allan Hills Blue Ice Area (BIA), and then to reconstruct details of past climate changes and greenhouse gas concentrations for certain time periods back to 2.5 Ma. Ice ages will be determined by applying emerging methods for absolute and relative dating of trapped air bubbles (based on Argon-40/Argon-38, delta-18O of O2, and the O2/N2 ratio). To demonstrate the potential of the Allan Hills BIAs as a paleoclimate archive trenches and ice cores will be collected for age intervals corresponding to 110-140 ka, 1 Ma, and 2.5 Ma. During the proposed two field seasons a total of 6x100 m and additional 15 m cores will be combined with trenching. The intellectual merit of the proposed activity is that the results of this work will extend the landmark work of EPICA and other deep ice coring efforts, which give records dating back to 0.8 Ma, and will complement work planned by IPICS to drill a continuous Antarctic ice core extending to 1.5 Ma. The results will help to advance understanding of major climate regimes and transitions that took place between 0-2.5 Ma, including the 40 kyr world and the mid-Pleistocene climate transition. A major long-term scientific goal is to provide a transformative approach to the collection of paleoclimate records by establishing an 'International Climate Park' in the Allan Hills BIA that would enable sampling of large quantities of known age ice as old as 2.5 Ma, by any interested American or foreign investigator. The broader impacts resulting from the proposed activity include training students who are well versed in advanced field, laboratory and numerical modeling methods combining geochemistry, glaciology, and paleoclimatology. We will include material relevant to our proposed research in our ongoing efforts in local education and in our outreach efforts for media. The University of Maine already has cyberinfrastructure, using state of the art web-based technology, which can provide a wide community of scientists with fast access to the results of our research. The work will contribute to the broad array of climate change studies that is informing worldwide understanding of natural and anthropogenic forced climate change, and the options for responding. This award has field work in Antarctica.